“Challenges Faced by Indian Learners in Chinese Language Acquisition and pedagogical implication for educators” (International Journal of Food and Nutritional Sciences, 2022)
The acquisition of the Chinese language by Indian learners presents a complex linguistic and cultural journey. This paper explore the challenges that Indian learners encounter when acquiring Mandarin Chinese as a second language. From tonal intricacies to pictographic characters, differences in sentence structure, and cultural nuances, Indian learners face a diverse range of obstacles that impact their language acquisition process. Through an exploration of these challenges, this paper aims to provide insights into the specific difficulties Indian learners encounter and offers pedagogical implications for educators to enhance the Chinese language learning experience.